2020
DOI: 10.4236/psych.2020.114042
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Ambition? Personality, Self-Perceived Leadership Potential, and the “Desire to Be Your Own Boss”

Abstract: This study focuses on the correlates of an individual's rating of their leadership potential. 1194 adults completed a six-factor High Potential work-related questionnaire and they also self-rated their leadership potential as well as their actual desire to become their own boss. Neither age nor sex was related to the two dependent variables, but nearly all the traits were. Stepwise regressions showed Competitiveness, Risk Approach and Conscientiousness were particularly related to self-related leadership poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The HPTI has received careful validation and been used in several published studies (Furnham and MacRae, 2020 ; Treglown et al, 2020a , b ). In a psychometric evaluation of this study Furnham and MacRae ( 2020 ) demonstrated that the internal reliability of each trait was satisfactory, as was the structure of the inventory, as assessed by confirmatory factor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The HPTI has received careful validation and been used in several published studies (Furnham and MacRae, 2020 ; Treglown et al, 2020a , b ). In a psychometric evaluation of this study Furnham and MacRae ( 2020 ) demonstrated that the internal reliability of each trait was satisfactory, as was the structure of the inventory, as assessed by confirmatory factor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding underlying ambition personality traits, investigations have examined the five-factor model and NEO personality factors (neuroticism [N], extraversion [E], openness [O], agreeableness [A], and conscientiousness [C]) and the six-factor HEXACO model (honesty-humility, emotionality, extraversion, agreeableness [ vs . Anger], conscientiousness, and openness to experience) (Judge and Kammeyer-Mueller, 2012; MacRae and Furnham, 2020; Treglown et al, 2020). In general, these studies show that ambition (measured in different ways) is associated with conscientiousness (diligence and prudence), extraversion (social boldness and liveliness), and low levels of social anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the results do suggest that personality factors play a part both in the desire to become a leader and in leadership emergence and efficacy (Treglown et al, 2020). This article suggested that two traits, hitherto ignored by the Big Five model, namely ambiguity acceptance and risk approach, maybe worth exploring further.…”
Section: Discussionmentioning
confidence: 96%